Key Factors of Prospective Students's Interest in Choosing a Study Program - Winarto - Winarto; Mustika - Widowati (Politeknik Negeri Semarang, 2023)
Study programs as products offered by universities are currently facing a very dynamic competitive situation. Managers are required to be able to understand the various things considered by prospective students and be able to meet their expectations. This article aims to develop a research model that is able to predict the antecedents of interest in prospective students enrolling in a particular study program. A literature review was conducted to build a research model that describes the antecedents of interest in enrolling in study programs. The results of the study show that job opportunities, quality and the environment of higher education are antecedents that have consequences on the interest in enrolling prospective students in a study program at a particular tertiary institution